Clinical value of (dedicated) 3 Tesla and 7 Tesla MRI for cT1 glottic carcinoma: A feasibility study. Issue 1 (15th January 2019) - van Egmond, Sylvia L.; Vonck, Bernard M.D.; Bluemink, Johanna J.; Pameijer, Frank A.; Dankbaar, Jan Willem; Stegeman, Inge; Philippens, Marielle E.P.; van den Berg, Cornelis A.T.; Janssen, Luuk M.; Terhaard, Chris H.
Abstract : Objective: To assess the feasibility of the clinical use of 3 Tesla and 7 Tesla Magnetic Resonance Imaging for early (cT1) glottic carcinoma, including structural assessment of technical image quality and visibility of the tumor; and if feasible, to correlate MRI findings to routine diagnostics. Methods: Prospective feasibility study. Twenty patients with primary clinical T1 glottic carcinoma underwent both routine clinical staging and CT. In addition, a 3 T and 7 T MRI protocol, developed for small laryngeal lesions, was performed in a 4‐point immobilization mask, using dedicated surface coils. Afterwards, routine endoscopic direct suspension laryngoscopy under general anaesthesia was performed. Results: Only 2 of 7 (29%) of 7 T MRI scans were rated as moderate to good technical image quality. After exclusion of three patients with only mild to moderate dysplasia at the time of MRI, 13 of 17 (76%) of 3 T MRIs were of adequate technical image quality. Tumor visualization was adequate in 8 of 13 (62%) of patients with invasive squamous cell carcinomas. With exclusion of the four MRIs with motion artefacts, the tumor and its boundaries could be adequately seen in 8 of 9 (89%) patients with squamous cell carcinoma versus only one in four (25%) of patients with carcinoma in situ lesions. Conclusions: 7 Tesla MRI was considered not feasible. 3 Tesla MRI, with adequate patient selection, namely clinical exclusion of patients with a history of claustrophobia and inclusion of only histologically proven invasive squamous cell carcinoma, can be feasible. Especially with further improvement of MR image quality. Level of Evidence: 2B, prospective diagnostic study